Meat and meat alternatives: where is the gap in scientific knowledge and technology? - Youling L. Xiong (Italian Journal of Animal Science)
The unprecedented surge of developing meat analogues and other alternative protein products in the past few years has occurred amidst numerous technological challenges. The creation of fibril structure and flavour from non-muscle proteinaceous sources to mimic fresh and processed meat requires a clear understanding of the fundamental differences between muscle and alternative proteins. Currently, plant-based meat alternatives are dominating the alternative market; mycoprotein-based products have also gained a market share, while algae and insects are other emerging sources of alternative proteins. Both traditional and novel processing technologies and innovative ingredient formulations are being developed to transform nonmuscle proteins into fibrous or particle structures that microscopically resemble muscle. However, the production of meat analogues generally entails ultra-processing and ultra-formulation, which could compromise nutritional value and safety. Therefore, to sustain the alternative protein market, scientists and entrepreneurs must methodically examine and understand inherent differences that separate alternative proteins from muscle proteins. An intuitive knowledge base is essential to designing new approaches to overcome technical challenges. In doing so, food scientists and entrepreneurs must be keenly cognisant that animal meat products are unique; the quality and sensorial attributes of meat can only be simulated but not replicated.